A sustainable approach to utilize sunflower seed powder as a fat replacer in cookies; effects on physicochemical, phytochemical, and sensory properties - Tusneem Kausar; Ashiq Hussain; Ammara Ainee; Nida Firdous; Adnan Ahmed; Rizwan Arshad; Shafiqa Ali; Ashiq Hussain; Aarzoo Sajid; Majid Majeed; Abdeen Elsiddig Elkhedir (Discover Sustainability)
Abstract Fat substitutes are important and sustainable ingredients to use in food industry to deliver some or all of the functional properties of the fat, while contributing less energy than the fat being replaced. Present study was planned to use sunflower seed powder (SSP) as a fat replacer, at concentrations of 10, 20, 30 and 40% (w/w, based on the shortening used) in the preparation of cookies, and assessed for various quality parameters (physical, chemical, phytochemical, functional and organoleptic). SSP showed ample amount of crude fat (35.62 ± 3.57%) and crude protein (19.58 ± 2.14%). Water and oil holding capacities of SSP were found 2.35 ± 0.51 g water/g SSP and 1.06 ± 0.23 g oil/g SSP, respectively. Use of SSP as a fat replacer significantly (p < 0.05) reduced the diameter and thickness of cookies, while increased the spread factor. Regarding proximate composition, a significant (p < 0.05) increase in moisture (from control to cookies with 40% SSP), (2.43 ± 0.18–3.58 ± 0.05%), crude protein (5.89 ± 0.18–9.26 ± 0.28%), crude fiber (0.78 ± 0.10–2.04 ± 0.03%), ash (0.52 ± 0.04–2.66 ± 0.11%) and decrease in fat (17.30 ± 0.16—15.82 ± 0.27%) and nitrogen free extract (72.86 ± 0.34–66.38 ± 0.31%) were resulted. Addition of SSP significantly (p < 0.05) increased the total phenolic content, total flavonoid content and total antioxidant activity in all the treatments, as compared to the control. The cookies prepared by using SSP as a fat replacer were found acceptable with respect to all sensory attributes. Hence, significant improvement in chemical composition and functional properties without affecting the consumer acceptability, reflects the potential of SSP for use as fat replacer in cookies.